PENGARUH PENGEMBANGAN KARIR, KOMPENSASI, MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PENDIDIKAN LABUHANBATU UTARA - Mawardani, Ika; Nasution, Novrihan Leily (LPPM Universitas Labuhanbatu, 2021)
This study aims to determine Career Development, Compensation, Motivation and Organizational Commitment to Employee Job Satisfaction at the North Labuhanbatu Education Office. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 30 respondents, while the population used in this study were employees at the North Labuhanbatu Education Office. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant test (t test), simultaneous significant testing (F test), and testing the coefficient of determination (R2). The results of this study indicate that partially (t test) it is known that Career Development has a positive and significant effect on Employee Job Satisfaction at the North Labuhanbatu Education Office with a tcount of 4.160 > ttable 1.710 and a significance level of 0.000 <0.05. Compensation has a positive and significant effect on employee job satisfaction at the North Labuhanbatu Education Office with a tcount value of 4.105 > ttable 1.710 and a significance level of 0.000 <0.05. Motivation has a positive and significant effect on employee job satisfaction at the North Labuhanbatu Education Office with a tcount value of 4.597 > ttable 1.710 and a significance level of 0.000 <0.05. Then Organizational Commitment has a positive and significant effect on Employee Job Satisfaction at the North Labuhanbatu Education Office with a tcount of 3.954 > ttable 1.710 and a significance level of 0.001 <0.05. In simultaneous testing (F test) it is known that Career Development, Compensation, Motivation and Organizational Commitment have a positive effect on Employee Job Satisfaction at the North Labuhanbatu Education Office with the results showing that the Fcount value is 28.005 > Ftable 2.76 and the significance level is 0.00 < 0.05. Through testing the coefficient of determination (Adjusted R Square) of 0.788 means 78.8%. Job satisfaction factors can be explained by Career Development, Compensation, Motivation and Organizational Commitment of 78.8%. While the remaining 21.2% is influenced by other variables not examined in this study.